Performance-Based Specifications and Control of Concrete Durability State-of-the-Art Report RILEM TC 230-PSC - Beushausen, Hans; Fernandez Luco, Luis (RILEM State-of-the-Art Reports, 2016)
This work gives an overview of significant research from recent years concerning performance-based design and quality control for concrete durability and its implementation. In engineering practice, performance approaches are often still used in combination with prescriptive requirements. This is largely because, for most durability test methods, sufficient practical experience still has to be gained before engineers and owners are prepared to fully rely on them.   This book, compiled by RILEM TC 230-PSC, is intended to assist efforts to successfully build the foundation for the full implementation of performance-based approaches through the exchange of relevant knowledge and experience between researchers and practitioners worldwide.  .